Lower limb muscle activity during table tennis strokes - Le Mansec, Y.; Dorel, S.; Hug, F.; Jubeau, M. (Sports Biomechanics, 2018)
This study aimed to compare the muscle activity of lower limbs across typical table tennis strokes. Fourteen high-level players participated in this study in which five typical strokes (backhand top, forehand top, forehand spin, forehand smash, flick) were analysed. Surface electromyography activity (EMG) of eight muscles was recorded (gluteus maximus, biceps femoris, vastus medialis, vastus lateralis, rectus femoris, gastrocnemius medialis, gastrocnemius lateralis, soleus) and normalised to the maximal activity measured during squat jump or isometric maximal voluntary contractions. The forehand spin, the forehand top and the forehand smash exhibited significant higher EMG amplitude when compared with other strokes. Both biceps femoris and gluteus maximus were strongly activated during the smash, forehand spin and forehand top (from 62.8 to 91.7% of maximal EMG activity). Both vastii and rectus femoris were moderately to strongly activated during the forehand spin (from 50.4 to 62.2% of maximal EMG activity) whereas gastrocnemii and soleus exhibited the highest level of activity during the smash (from 67.1 to 92.1% of maximal EMG activity). Our study demonstrates that offensive strokes, such as smash or forehand top, exhibit higher levels of activity than other strokes.